Background soundscapes influence the perception of ice-cream as indexed by electrophysiological measures - Xu, Y; Hamid, N; Shepherd, D; Kantano, K; Reay, S; Martinez, G; Spence, C (Elsevier, 2019)
Listening to specific soundscapes can influence multisensory flavour perception. In the present study, changes in people's perception of the flavour of ice-cream were tracked over time as they listened to a café soundscape, and when this soundscape was overlaid with either bird, machine, or forest soundscapes. In addition, emotions and electrophysiological measures were recorded in order to help understand any changes in taste/flavour perception. The results of Temporal Dominance of Sensation (TDS) analysis revealed that cocoa was dominant early in the consumption episode while listening to the control café soundscape. Sweetness and creaminess were dominant at the start of the consumption episode while listening to the café-forest soundscape. Creaminess was dominant at the start of the consumption episode while listening to the café-bird soundscape. Bitterness was perceived at the end of the consumption period while listening to the café control and café-machine soundscapes. These findings demonstrate the crossmodal influence of audition on perception in the chemical senses. As expected, negative emotions were significantly higher when listening to the machine soundscape, while positive emotions were significantly higher when listening to café-forest and café-bird soundscapes. Evaluating ice-cream while listening to the café-machine soundscape evoked negative emotions associated with bitterness and creaminess, that were also associated with increased heart rate (HR) and respiration rate (RESP). When listening to the café-forest soundscape, ice-cream was associated with sweetness, and positive emotions (e.g., love, satisfaction, happiness, amusement and enjoyment). This might have led to increased blood volume pulse (BVP) amplitude, which is itself indicative of a relaxed state. Enhancing eating experiences by means of atmospheric soundscapes that are designed specifically to accentuate specific aspects of multisensory taste/flavour perception is currently an area of interest in the food sciences literature and will likely lead to future commercial applications.